Clinical Aspects of the Oral Cavity in Patients with Psoriasis: An Initial Study and a Proposal of a New Evaluation Method. (September 2013) - Carboni, I.; Maurici, M.; Bonatti, C.; Specchio, F.; Salvatori, C.; Docimo, R.; Chimenti, S.; Tamburi, F.; Franco, E.; Nisticò, S.
The involvement of the oral cavity is rare but possible in patients with psoriasis. Most frequently different clinical entities are reported such as geographic tongue, fissures, angular cheilitis and ectopic geographic tongue. This interdisciplinary study was conducted by dermatologists in collaboration with dental hygienists on 22 patients with psoriasis. We examined 11 men and 11 women aged between 25 and 72 years during a period of 6 months. The involvement of the oral cavity was examined and a full photographic evaluation was carried out. A new assessment evaluation named Oral Psoriasis Area and Severity Index (OPASI) is proposed herein. The results obtained show the presence of oral lesions in 45.6% of the cases. This high involvement could be explained by the interdisciplinary nature of the study. We believe OPASI can be useful to assess the severity of lesions of the oral cavity, and may help to evaluate the response to therapy in relation to the Psoriasis Area and Severity Index (PASI) improvement.